Tradeoffs between thinning treatments and rotation periods of planted Larix olgensis forests: a perspective from carbon balance - Lin, Xueying; Lu, Wei; Dong, Lingbo (Frontiers in Forests and Global Change, 2024)
IntroudctionThe current CO2 levels are higher than ever in the past two million years. Forests, as one of the climate change mitigation solutions, are becoming increasingly technically feasible and cost-effective. However, limited research comprehensively considers thinning in the context of optimizing the rotation period for carbon sequestration.MethodsThis study utilizes stand-level growth models and diameter distribution models to simulate the carbon balance dynamics of Larch (Larix olgensis) plantations under various thinning scenarios. The effects of different initial planting densities (N0∈{2,500, 3,333, 4,444} tree ha−1) and site class index (SCI∈[14–20] m) on the optimal forest management measures are also quantified.ResultsThe results reveal that the overall trend of carbon balance gradually increases and then decreases over time under the baseline scenario (3,333 tree ha−1 of N0, 16 m of SCI, 5% of discount rate, 100 CNY ton−1 C of carbon price); the carbon balances of all thinning forests were less than that of the unthinned forest before until 56th year. The optimal rotation period and net present value (NPV) increase with increasing thinning frequency and intensity. The sensitivity of NPV to thinning frequency increases with higher thinning intensities, SCI, and carbon prices.DiscussionThis study further expands the scope of forest management strategies, providing optimal forest management plans for all 21 combinations of different SCIs and N0. The optimal forest management strategy in the baseline scenario is 3 thinnings, with the first thinning at 20% intensity in the 15th year, the second thinning at 30% intensity in the 18th year, and the third thinning at 30% intensity at 21 years, with a rotation period of 26 years, resulting in an NPV of 37,180 CNY ha−1.